Effects of dietary fermented peony seed dreg on the laying performance, albumen quality, antioxidant capacity, and n-3 PUFA-enriching property of laying hens - Wan, Yi; Ma, Ruiyu; Qi, Renrong; Lu, Jing; Wang, Zaigui; Ma, Qiugang; Liu, Wei; Li, Junying; Li, Yan; Zhan, Kai (Frontiers in Veterinary Science, 2023)
Introduction It is of great importance to seek agro-industrial byproducts that can serve as unconventional or alternative feedstuffs for poultry, especially those that are substitutive sources of n-3 polyunsaturated fatty acids (PUFAs), as this will contribute to alleviating feed shortage pressure and improving poultry performance and product quality. In this study, the effects of dietary fermented peony seed dreg (FPSD) on the production performance of hens and fatty acid composition of meat and egg yolk were evaluated. Methods A total of 480 54-week-old Xinyang chickens were divided into 5 groups: control (basal diet); 5% peony seed dreg (PSD); and 5%, 7% and 9% FPSD, and each group consisted of 6 replicates with 16 birds per replicate. Production performances were recorded daily, and egg quality, serum parameters, antibody titers and fatty acid profile in the muscle and yolk were measured at 64 weeks of age. Results and discussion Egg production, feed conversion ratio and egg albumen quality were improved (p < 0.05) by 5% and 7% FPSD groups compared to 5% PSD and the control diet. Immune status was not influenced by PSD, but antibody titres against H7N9 and ND were improved by FPSD diets during most of the experimental periods. Dietary 5% and 7% FPSD increased (p < 0.05) serum high density lipoprotein concentrations and glutathione peroxidase actives. Total n-3 polyunsaturated fatty acids (PUFA) in meat and yolk increased gradually, while the total saturated fatty acids (SFA) and the n-6/n-3 PUFA ratio decreased gradually with increasing dietary FPSD levels. In conclusion, up to 7% dietary FPSD has the potential use to be utilized as a supplement in Xinyang laying hen diets to produce n-3 PUFA-enriched meat and eggs and positively affect production performance and health status.